Evaluasi Ketersediaan Pelayanan dan Pendokumentasian Klinik Pratama Korpagama UGM untuk Melakukan Kerja Sama dengan BPJS tahun 2014 - , ULFA OKTAFIANI; , dr. Wahyudi Istiono, M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Applicability of the National Social Security System in 2014 is expected to improve the health of the people of Indonesia. For that in the face of the National Social Security System is needed and a good preparation of all the elements involved, both the agency designated Social Security Agency (BPJS), government, health care facilities and providers, both in the first and /or advanced levels so that the program can running smoothly and well. Family Doctor Clinic Korpagama as one of the organizers of the first-level health facilities were recently transformed into Primary Clinic and will cooperate with the Social Security Agency of Health should have good preparation, especially in the availability of services and documentation in order to follow the success of the implementation of Security System the National Social. Objective: Evaluate the readiness of Primary Clinical Korpagama Gadjah Mada University in terms of the availability of services and documentation for working with the Social Security Agency (BPJS) in 2014 Methods: This study used a qualitative descriptive method with cross-sectional design. Retrieval of research data through interviews, documentary studies, and observation. Results: The results of this study indicate that the readiness Korpagama Clinic Family Physicians in cooperation with the Social Security Agency (BPJS) in 2014 in terms of the availability of most of the existing services and in accordance with the Social Security Agency of Health (BPJS) regulations, the availability of services relating to the administration